Comparison of breast cancer recurrence risk and cardiovascular disease incidence risk among postmenopausal women with breast cancer - Bardia, Aditya (2011)
The majority of breast cancers are diagnosed in postmenopausal women. Competing comorbidities, particularly cardiovascular disease (CVD), should be considered when individualizing adjuvant therapies for these women. We compared the 10-year predicted breast cancer recurrence risk with CVD risk among postmenopausal women with hormone receptor-positive (HR+), non-metastatic breast cancer. CVD risk factor data were prospectively collected from postmenopausal women with stage I-III, HR+ breast cancer initiating adjuvant aromatase inhibitor therapy. We compared predicted 10-year CVD risk, including the composite index heart age, computed from modified Framingham risk score, with predicted 10-year risk of breast cancer recurrence using Adjuvant! Online. We created multivariable logistic regression models to estimate the odds ratios (OR) and 95% confidence intervals (CI) for greater CVD risk than breast cancer recurrence risk. Among 415 women, mean age and heart age were 60 and 67 years, respectively. Overall, 43% of women had a predicted 10-year CVD risk equivalent to breast cancer recurrence risk and 37% had CVD risk higher than breast cancer recurrence risk. Predicted CVD risk was higher than breast cancer recurrence risk for stage I disease (OR: 6.1, 95% CI: 3.4–11.2) or heart age >65 (OR: 12.4, 95% CI: 7.0–22.6). The majority of postmenopausal women with HR+ early breast cancer had a predicted 10-year CVD risk that was equivalent to or higher than breast cancer recurrence risk. Physicians should weigh competing risks and offer early screening and cardiac prevention strategies for women at a greater risk for CVD.